PP14 GP Sim- Primary care emergency simulations in-situ for clinical and non-clinical staff. A years experience. (10th November 2020) - Mason, Timothy; Bartle, David; Thompson, Ross; Schwinge, Rene; Janoff, Sam; Rochester, Helen
Abstract : Background: Within every GP pracice there are a wide range of staff who may be the first to encounter a challenging situation with an unwell patient. Ensuring that the whole GP practice functions as a team will only happen if they train for this as a team. Teams within general practice are a microcosm of the NHS and a familiarity of systems within this are vital. A recent systematic review suggests that in-situ simulation training improves patient outcomes. 1 The use of Simulation to practice medical emergencies within primary care for clinical and non-clinical teams has been reported on before as part of a course 2 but not in an in-situ setting. We present our experiences and feedback of our year simulating medical emergencies in primary care. Summary of Educational Project: In 2019–2020, through funding from Health Education England the Royal Devon and Exeter (RD&E) Hospital simulation team ran multiple simulation sessions within Primary care. Each session was delivered within a general practice clinical area. A post-scenario debrief, was conducted with each team highlighting the learning from the training and action planning to improve patient safety in subsequent emergencies. Afterwards we sent the practice these learning points along with photographs of the sessions. Scenarios included opiate overdose, SVT, Asthma, anaphylaxis and seizure. We used actors and a range of manikins as patients. Feedback post scenario was collected with Likert scales on acceptability of the session, confidence and other qualitative measures. Summary of Results: Simulations took place in 10 settings, 9 GP practices and 1 emergency service, with 118 participants. This included staff in 9 different job roles (clinical and non-clinical) from managers to paramedics. Over 95% of participants rated that the training had improved their confidence in skills and in managing acutely unwell patients in their workplace setting. Universally despite large debriefing groups these were teams that were open and reflective with each other. Feedback highlighted that it was vital to use their own equipment and in many practices this led to either restructuring of resuscitation trolleys or further training. It also provided a safe space for clinical and non-clinical staff to discuss better ways of helping and communicating with each other. Conclusions/Recommendations: In-situ medical emergency simulation for clinical and non-clinical staff within Primary care, is a popular and confidence building form of training which helps test systems and gives a platform for all Primary care staff to communicate. Reference: Lamb EI, Jenkins N, Male P, et al. Primary care emergencies: improved confidence in clinical and non-clinical members of the multidisciplinary team using a simulation programme. BMJ Simulation and Technology Enhanced Learning 2019;5:192–193.